2018
DOI: 10.1080/23337931.2018.1476869
|View full text |Cite
|
Sign up to set email alerts
|

Presence and leaching of bisphenol a (BPA) from dental materials

Abstract: BPA has been reported to leach from some resin based dental restorative materials and materials used for orthodontic treatment. To confirm and update previous findings, especially in light of the new temporary lower threshold value for tolerable daily BPA intake, we have investigated the leaching of BPA from 4 composite filling materials, 3 sealants and 2 orthodontic bonding materials. The materials were either uncured and dissolved in methanol or cured. The cured materials were kept in deionized water for 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 22 publications
1
23
0
4
Order By: Relevance
“…Among EDs, bisphenol A (BPA) is widely used as a component of epoxy resins and polycarbonate plastics by industry. BPA is present in plastic food containers, metal cans as epoxy coatings, kitchenware toys, medical devices, and dental composites and sealants [2]. In humans, BPA has been shown to have developmental, reproductive, cardiovascular, immune, and metabolic adverse outcomes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Among EDs, bisphenol A (BPA) is widely used as a component of epoxy resins and polycarbonate plastics by industry. BPA is present in plastic food containers, metal cans as epoxy coatings, kitchenware toys, medical devices, and dental composites and sealants [2]. In humans, BPA has been shown to have developmental, reproductive, cardiovascular, immune, and metabolic adverse outcomes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the amounts of released BPA measured herein were comparable with those reported by Suzuki et al [ 15 ], but higher than values reported by Watanabe [ 16 , 17 ]. They were also considerably higher than in recent studies that investigated the release of BPA from dental composites in methanol [ 22 ], artificial saliva [ 24 ], and distilled water [ 27 ].…”
Section: Discussionmentioning
confidence: 64%
“…In another in vitro study, Eliades et al in 2011 [42] found the highest concentration of BPA in Transbond™ XT (3M, St. Paul, Minneapolis, MN, USA) in the 1 month group (2.9 mg/L) [42]. American Dental association (ADA) Science Institute recently analyzed 12 dental sealants and concluded that they showed extremely low BPA release (0.09 nanograms of BPA in four teeth applications) [43]. Becher et al in 2018 [43] analyzed three pit and fissure sealants: Clinpro TM Sealant (3M, St. Paul, Minneapolis, MN, USA), Delton ® (Dentsply Sirona, York, PA, USA) and Helioseal ® F (Ivoclar Vivadent Inc., New York, NY, USA).…”
Section: Discussionmentioning
confidence: 99%
“…American Dental association (ADA) Science Institute recently analyzed 12 dental sealants and concluded that they showed extremely low BPA release (0.09 nanograms of BPA in four teeth applications) [43]. Becher et al in 2018 [43] analyzed three pit and fissure sealants: Clinpro TM Sealant (3M, St. Paul, Minneapolis, MN, USA), Delton ® (Dentsply Sirona, York, PA, USA) and Helioseal ® F (Ivoclar Vivadent Inc., New York, NY, USA). This study compared the leached BPA values obtained by uncured materials and cured materials and it was confirmed that Delton (Dentsply Sirona, York, PA, USA) was the one cured material with BPA levels significantly above the control levels and showed the highest BPA leaching after 24 h (9.6 ± 2.2 ng/mL), in an immersion medium of deionized water without hydroquinone, which is maintained during the following 15 days [43].…”
Section: Discussionmentioning
confidence: 99%